Interaction between 12p chromosomal abnormalities and Lnc‐HOTAIR mediated pathway in acute myeloid leukemia. Issue 9 (30th April 2019) - El‐Khazragy, Nashwa; Ghozy, Sherief; Matbouly, Safa; Zaki, Walid; Safwat, Gehan; Hussien, Ghada; Khalifa, Omar
Abstract: Objectives: To investigate the correlation of homeobox (HOX) transcript antisense RNA expression with clinicopathological features and the clinical prognosis of the patients with chromosome 12p abnormalities associated acute myeloid leukemia (AML). We also investigate the association of 12p chromosomal on the expression of HOTAIR, miRNA‐193a, and c‐kit gene as targeting genes for HOTAIR in AML. Methods: AML patients with 12p chromosomal abnormalities were recruited and compared to AML with other chromosomal abnormalities rather than 12p. The long noncoding RNA (lncRNA) "HOTAIR, " miR‐193a, and c‐Kit genes expression were measured in bone marrow samples using Syber green based real‐time polymerase chain reaction. Results: We found a significant difference for the expression levels of HOTAIR, c‐kit, and miR‐193a between 12p abnormalities associated AML and those without. The survival analysis revealed that patient's with low expression levels of HOTAIR and c‐kit had significantly better survival and leukemia free survival. In contrast, miR‐193a was associated with better overall survival but not leukemia free survival. Conclusion: 12p abnormalities associated AML were associated with worse prognosis. Our results proved that HOTAIR, miR‐193a, and c‐kit genes are independent prognostic predictors in 12p chromosomal associated AML; therefore it may represent a novel therapeutic application in AML in the future. Abstract : To investigate the correlation of homeobox (HOX) transcript antisense RNA expression with clinicopathological features and the clinical prognosis of the patients with chromosome 12p abnormalities associated AML. We also investigate the association of 12p chromosomal on the expression of HOTAIR, miRNA‐193a, and c‐kit gene as targeting genes for HOTAIR in AML.12p abnormalities associated AML were associated with worse prognosis. Our results proved that HOTAIR, miR‐193a, and c‐kit genes are independent prognostic predictors in 12p chromosomal associated AML; therefore it may represent a novel therapeutic application in AML in the future.